Kingdom of the Netherlands-Netherlands : Publication of Financial Sector Assessment Program Documentation: Detailed Assessment of Observance on Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2011)
Significant legislative changes and regulatory developments have taken place in the Netherland's insurance sector. The initial Financial Sector Assessment Program (FSAP) and the current assessment are benchmarked against the Insurance Core Principles (ICPs) issued in 2003. Progress has been made in addressing the recommendations arising from the assessment. The Financial Institutions Risk Analysis Method (FIRM) and the introduction of macroprudential supervision have strengthened The NetherlandsCentral bank's (DNB) risk-based supervision and market analysis. The updated regulatory framework has a high level of observance and the government has strengthened macro-prudential supervision to complement the traditional supervision approach.